Analisis Dukungan Sosial untuk Anak Pekerja Migran Indonesia dengan Convoy Model - Gusman Yuherina (Parahyangan Center for International Studies, 2026)
Law No. 18/2017 on the Protection of Indonesian Migrant Workers stipulates that protection before, during, and after migration should extend not only to migrant workers but also to the families left-behind. In practice, however, children of migrant workers often receive limited and uneven support while a parent, most commonly the mother, works abroad. This study examines the structure and perceived adequacy of social support for left-behind children in a major migrant-sending region of Indonesia using the Convoy Model of Social Relations. A qualitative design was employed, drawing on structured interviews with 100 left-behind children (aged 7–20) in Kertasemaya and Kenanga villages, Indramayu Regency. Participants were selected through purposive sampling and the data were analyzed using hierarchical convoy mapping (inner, middle, and outer circles) to identify key actors and support functions. Findings show that peers occupy the inner circle and constitute the most frequently accessed source of everyday emotional support. Mothers and grandmothers appear in the middle circle, reflecting their continued importance despite geographic distance, communication constraints, and caregiving limitations shaped by resources and generational gaps. A substantial share of children reported self-reliance, suggesting coping strategies that may indicate both adaptive independence and emotional withdrawal. Fathers and extended kin were positioned largely in the outer circle, and support from relatives on either parental side was minimal. While government agencies, NGOs, and religious organizations provided assistance, especially during the COVID-19 period, children generally perceived institutional support as predominantly material and episodic, and rarely sought help for private or psychosocial difficulties. This study contributes to the literature by applying convoy mapping to children’s accounts of support in transnational migrant families in Indonesia, highlighting a persistent gap between instrumental assistance and relationship-based psychosocial support. The findings underscore the need to strengthen community parenting and early intervention mechanisms such as building trust, accessible adult mentorship, and caregiver capacity within programs. Keywords: left-behind children; Indonesian migrant workers; social support; convoy model; community parenting; early intervention